Sustainability communication and its effect in consumer intention to visit a tourist destination - Francisco Vicente Sales Melo; Salomão Alencar de Farias (Tourism & Management Studies)
This article investigated if the rational and hedonic of sustainability stimuli inserted in communications of touristic leisure destinations, moderated by emotions, involvement and ecological awareness are related to the consumer intention to visit a tourist destination. The research was made through an experimental design with manipulation between groups. Text messages manipulated the sustainability stimuli, and presented only one manipulated condition to each participant. It was found that the hedonic sustainability stimuli have a stronger effect over the consumer’s intention, especially to those with low ecological awareness. The study contributes to literature by revealing that despite the emotion constructs and the fact that ecological involvement and awareness are not strong moderators in the relation between rational or hedonic sustainability stimuli and intention, they are aspects that, when positively activated, especially from hedonic arguments of sustainability, generate greater intention to visit destination by the consumer.